El Clima organizacional y mejoramiento de la satisfacción laboral de los trabajadores de la Municipalidad Provincial de Trujillo - 2012 - Campos Ríos, Sandra Stephanie (2012)
The present study aimed to measure the influence of organizational climate on job satisfaction Workers of the Provincial Municipality of Trujillo 2012. The study developed as a descriptive research - transeccional of a single box. The sample consisted of 85 workers of the Provincial Municipality of Trujillo. For data collection was used as technique the survey, through a questionnaire, structured in a series of 40 items, qualified by a Likert scale of 5 points. For data analysis were using tables and graphics, also was analyzed according to the Likert scale, for a better understanding of these results. According to the results it is concluded that the organizational climate influences slightly on job satisfaction Workers of the Provincial Municipality of Trujillo. Therefore we present a proposal to improve the organizational climate to achieve an improvement in job satisfaction.